Genome-wide association study for the level of prolificacy in Cameroon’s native goat - Simo, J.K.; Meutchieye, F.; Wouobeng, P.; Tarekegn, Getinet M.; Mutai, Collins; Nandolo, W.; Pelle, Roger; Djikeng, Appolinaire; Manjeli, Y. (Informa UK Limited, 2024)
Income from goats highly depends on prolificacy, which is difficult to improve by traditional breeding methods. The study aimed to identify SNP markers for prolificacy, using a case–control genome-wide association study (GWAS) on 111 genotyped Cameroon native goat (CNG) does, based on the 50 K single nucleotide polymorphism (SNP) chip panel. None of the top SNPs reached the significant p-value of 5 × 10−8. The highest p-value was 0.0009. Despite the number of cases being about a quarter of the number of controls, the highest allele frequency of some of the top 20 variants in the cases was indicative of their potential role in the trait. These top variants included the following 15: rs268285661, rs268235169, rs268236449, rs268235135, rs268240394 in Sphingosine-1-phosphate phosphatase 2 (SGPP2) gene, rs268283635 in Solute carrier family 24 member 2 (SLC24A2) gene, rs268251678 in Androgen-induced gene 1 (AIG1) gene, rs268267018, rs268239617, rs268281364, rs268273029, rs268286941, rs268236144, rs268233233 in CEP126 gene and rs268278159, respectively. Our findings indicate that GWAS enable the identification of some loci within genes, with known biological functions and pathways in human being and mice animal model but far-ranging to what was previously hypothesized and tested in goat.